You can factor the 32 out of the sum:
![\displaystyle \sum_(m=1)^\infty 32 \cdot \left((1)/(2)\right)^(m-1) = 32\sum_(m=1)^\infty \left((1)/(2)\right)^(m-1)](https://img.qammunity.org/2020/formulas/mathematics/college/pgz0p3u566hpl84nniypha40t1f5fhmw43.png)
We can also change the index as follows
![\displaystyle 32\sum_(m=1)^\infty \left((1)/(2)\right)^(m-1) = 32\sum_(m=0)^\infty \left((1)/(2)\right)^(m)](https://img.qammunity.org/2020/formulas/mathematics/college/zhjr3yc23qhuwe96b38kr320rxan9vpn32.png)
Now, we have a theorem that states that the series
![\displaystyle \sum_(m=1)^\infty a^m](https://img.qammunity.org/2020/formulas/mathematics/college/gjmfjbmxkdrqy6win7lxeyk32l9i636jiq.png)
converges if and only if
, and in this case we have
![\displaystyle \sum_(m=1)^\infty a^m = (1)/(1-a)](https://img.qammunity.org/2020/formulas/mathematics/college/q6hmh1sf0x003od07jonshlaxjytje02ur.png)
This is your case, because you have
![|a|=(1)/(2)<1](https://img.qammunity.org/2020/formulas/mathematics/college/t78e8sjxxqeda7okf4gic6hef784kxhv1x.png)
which implies that your series converges, and the value is
![\displaystyle 32\sum_(m=0)^\infty \left((1)/(2)\right)^(m) = 32 \cdot (1)/(1-(1)/(2)) = 32\cdot 2 = 64](https://img.qammunity.org/2020/formulas/mathematics/college/6ahtexilfndsuhq1wmgraphpehgw1wqlzl.png)